Comparison of walkability in different urban districts using space syntax - Roozkhosh, Farnoosh; Molavi, Mehrnaz; Salaripour, Aliakbar (Journal of Architecture and Urbanism, 2020)
The expansion of cities and increasing car traffic have brought problems such as increased greenhouse emission, noise pollution, and access problems that makes sustainable urban development one of the most significant concerns of urban governors. Obviously, the utilization of public transportation and walkability is one of the highly significant aspects of sustainable development. In an effort for the recognition of urban districts of Bojnourd, the current article compares the extent of walkability in each district. To investigate the walkability index using the opinions of experts and scholars 4 criteria and 22 sub-criteria were taken into consideration. In this regard, the ANP approach was also applied to improve decision making and grading the importance of criteria; districts were finally graded using the TOPSIS model concerning walkability. In the present study as an applied one, field surveys, questionnaires, library studies, and documents were the data collection tools. The findings revealed that the old district (central), have the highest walkability potential in comparison to medial, and the new development districts respectively. Since the old district has the highest amount of mixed land uses, passage connectivity, passage integration, public transport, and so forth, it can be concluded that walkability is closely related to the mentioned factors.